Descripción de la pesquería artesanal de peces, en tres puertos pesqueros de la IV región, Coquimbo, Chile (ING) - Víquez Portuguez, Rigoberto; Acuña Soto, Enzo (Uniciencia, 2002)
For this study, the small fishing ports of Coquimbo, Guanaqueros, and Tongoy of the IV Region of Chile, were closely monitored. The data was taken from June 1995 to June 1996, by means of an agreement between the Federation of Workers of the Sea (FETRAMAR) of the Elqui province F.G., the National Fisheries Service of the IV Region of Chile (SERNAP), and the Catholic University of the North. Several studies were done on the species, captured and landings; as well as of the different fishing techniques and tools used in the small fishing ports. A total of 27 species of commercial interest were captured by the artisanal fishing fleet. The most relevant species for their capture during the period of study were the anchovy (Engraulis ringens), the jack mackerel (Trachurus murphyi), captured with purse seine nets. The hake (Merluccius gayi) and the pomfret (Brama australis) captured with long line. Besides, the other fishing techniques and of fishery tools utilized in the small fishing ports were determined. Furthermore, the traditional fishing fleet which acts over the species in questions was defined, described and characterized.